Sankt-Peterburg of Peter I: The History of Household Possession — Site Development, Owners and Builders by Mariia V. Nikolaeva. Moscow: Progress-Traditsiia Publ., 2014 - Stanyukovich-Denisova, Ekaterina Yu. (Actual Problems of Theory and History of Art, 2015)
The article is a brief presentation of the voluminous book by the Moscow archivist and historian of architecture Mariia V. Nikolaeva Sankt-Peterburg of Peter I: The History of Household Possession —Site Development, Owners and Builders, released in Russian by the Progress-Tradition Publ. in 2014. It is a successful combination of scientific research and publication of archival documents (from the RGADA funds) clearly seen in the book structure. Comprehensive introductory part, in addition to the “Foreword”, includes chapters “The Sources Survey”, “The Archeographic Entry” and “An Essay on the History of Private Construction in St. Petersburg of Petrine time”. The first part of the monograph contains a detailed analysis of house possession on the Vasilieskii isle and along the Neva embankments of Admiralteiskii and Gorodskoi islands and Moskovskaia district. In the second part Nikolaeva lists the contract registers and cites their text. A lot of black-and-white reproductions of plans and drawings of the first half of the 18th century is an essential part of the research. The vast application comprises a glossary, an index, a list of abbreviations. The relevance of the book lies not only in introducing into the scientific use and a deeply serious and compelling analysis of new documents on the history of the Petrine Petersburg architecture, but also, first and foremost, in fixing the household possession topics in modern Russian historiography and developing methods of its comprehensive studies.
Keywords: St. Petersburg architecture; Petrine time; common residential construction; Mariia Valentinovna Nikolaeva; history of household possession